(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2017)
Abstract: This paper proposes to reconstruct some epistemological assumptions of two contemporary authors: Boaventura de Sousa Santos and Immanuel Wallerstein. Both authors ground, on their own path, a critique of the model of science that was consolidated in the 19th century, based on questionable epistemological assumptions, especially in face of the complex emerging realities in Latin America. What are the main criticisms made about the hegemonic science model? What are the perspectives that these two authors indicate, especially regarding the social sciences, in order to effectively contribute to ground an epistemology that is able to capture the complex and contradictory historical processes? Aiming to deal with these challenges, this paper begins with a general introduction to contextualize the discussion. After that, the text deals with the reconstruction of each author’s individual main arguments and concludes emphasizing the potentialities of these contributions to ground an epistemology that is able to have a dialog with different areas of knowledge, in order to contribute with the educational policies in Latin America, with regard to the past and the future. Keywords: Educational Policy. Epistemology. Boaventura de Sousa Santos. Immanuel Wallerstein.